IL-10 and TGF-β1 may weaken the efficacy of preoperative anti-tuberculosis therapy in older patients with spinal tuberculosis - Li, Shanshan; Wu, Runrui; Feng, Mengru; Zhang, Hong; Liu, Dongxu; Wang, Fenghua; Chen, Wen (Frontiers in Cellular and Infection Microbiology, 2024)
Spinal tuberculosis is a common extrapulmonary type that is often secondary to pulmonary or systemic infections. Mycobacterium tuberculosis infection often leads to the balance of immune control and bacterial persistence. In this study, 64 patients were enrolled and the clinicopathological and immunological characteristics of different age groups were analyzed. Anatomically, spinal tuberculosis in each group mostly occurred in the thoracic and lumbar vertebrae. Imaging before preoperative anti-tuberculosis therapy showed that the proportion of abscesses in the older group was significantly lower than that in the younger and middle-aged groups. However, pathological examination of surgical specimens showed that the proportion of abscesses in the older group was significantly higher than that in the other groups, and there was no difference in the granulomatous inflammation, caseous necrosis, inflammatory necrosis, acute inflammation, exudation, granulation tissue formation, and fibrous tissue hyperplasia. B cell number was significantly lower in the middle-aged and older groups compared to the younger group, while the number of T cells, CD4+ T cells, CD8+ T cells, macrophages, lymphocytes, plasma cells, and NK cells did not differ. Meaningfully, we found that the proportion of IL-10 high expression and TGF-β1 positive in the older group was significantly higher than that in the younger group. TNF-α, CD66b, IFN-γ, and IL-6 expressions were not different among the three groups. In conclusion, there are some differences in imaging, pathological, and immune features of spinal tuberculosis in different age groups. The high expression of IL-10 and TGF-β1 in older patients may weaken their anti-tuberculosis immunity and treatment effectiveness.